UPAYA MENINGKATKAN HASIL BELAJAR ILMU PENGETAHUAN ALAM DENGAN PENERAPAN METODE DEMONSTRASI SISWA KELAS IV SD NEGERI 010 BANJAR PANJANG KECAMATAN KERUMUTAN - Deden Kusdinar (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2017)
Based on the author's experience teaching for this in SD Negeri 010 Banjar Panjang Kerumutan, and based on observation and early reflections by the author seen low creativity of students in learning that ultimately ends up in the low student learning outcomes themselves, especially on the subjects of Natural Sciences. After many tests on the midterm turns lower student learning outcomes. Completeness class only reach 50% or 10 out of 20 students, KKM for subjects of Natural Sciences which has been set in the class IV SD Negeri 010 Banjar Panjang Kerumutan is the number 70. As Judge things that cause children low value, from the aspect of teachers are: teacher always using methods lectures, learning achievement of children have been considered equally by teachers, and the learning process is dominated by the teacher. This research is a classroom action research (PTK). Class action research through the stages of planning, implementation, observation and reflection. From the research data is a result of learning of natural science at the top can be seen learning outcome science students from the action on the preliminary data for the first cycle to the second cycle by improving student learning outcomes that menigkat are significant, the initial data of students who achieve mastery only 50 % and cycle to the first increase has reached 70% and the thoroughness of the class in the second cycle reaches 85%.